2011
DOI: 10.1523/jneurosci.0257-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Evidence for Direct Corticospinal Contributions to Control of the Ipsilateral Forelimb in Monkey

Abstract: Strong experimental evidence implicates the corticospinal tract in voluntary control of the contralateral forelimb. Its potential role in controlling the ipsilateral forelimb is less well understood, although anatomical projections to ipsilateral spinal circuits are identified. We investigated inputs to motoneurons innervating hand and forearm muscles from the ipsilateral corticospinal tract using multiple methods. Intracellular recordings from 62 motoneurons in three anesthetized monkeys revealed no monosynap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 64 publications
(86 reference statements)
8
85
1
1
Order By: Relevance
“…This is in good agreement with invasive studies on primates and informs of similar neural processing in humans. The observed laterality of ERPs is also compatible with the view of relatively direct role of contralateral motor cortex (Soteropoulos et al, 2011) in execution of tasks and participation of both ipsilateral and contralateral hemispheres in preparation and planning (Schaal et al, 2004). These findings suggest that PM/SMA is active in early preparation; PC activity is added for direction-dependent processing; and M1 activity is mostly related to generation of descending neural motor commands.…”
Section: Potential Neural Processing Mechanismssupporting
confidence: 86%
“…This is in good agreement with invasive studies on primates and informs of similar neural processing in humans. The observed laterality of ERPs is also compatible with the view of relatively direct role of contralateral motor cortex (Soteropoulos et al, 2011) in execution of tasks and participation of both ipsilateral and contralateral hemispheres in preparation and planning (Schaal et al, 2004). These findings suggest that PM/SMA is active in early preparation; PC activity is added for direction-dependent processing; and M1 activity is mostly related to generation of descending neural motor commands.…”
Section: Potential Neural Processing Mechanismssupporting
confidence: 86%
“…However, a significant ipsilateral response was predominantly recorded in proximal or truncal muscles upon stimulation of SMA [44, 45], and, occasionally, M1 [43]. In vivo cortical stimulation studies performed in rhesus [24] and marmoset monkeys [42] showed that ipsilateral M1 projections are not monosynaptic. Although the lack of monosynaptic connection is not unanticipated given that the majority of contralateral fibers also do not monosynaptically connect to motor neurons, the presence of polysynaptic connections does not rule out the involvement of the contralateral hemisphere or contralateral brainstem nuclei upon stimulation of ipsilateral cortical regions.…”
Section: Icst In Non-human Primatesmentioning
confidence: 99%
“…Neuroanatomically, one cerebral hemisphere is responsible for motor function of the contralateral body side; however, some fibers play a key role in ipsilateral movements [76]. In poststroke subjects, motor impairment may also arise on the ipsilesional or same side of the body but not as severe as on the contralesional body side [77,78].…”
Section: Role Of the Less-affected Sidementioning
confidence: 99%
“…Sur le plan neuro-anatomique, un hémisphère cérébral est chargé de la fonction motrice du côté controlatéral du corps ; cependant, certaines fibres ont un rôle clé dans les mouvements ipsilatéraux [76]. Chez les patients post-AVC, la déficience motrice peut aussi survenir sur le côté ipsilésionnel du corps mais elle n'est pas aussi sévère que celle du côté contralé-sionnel [77,78].…”
Section: Rôle Du Côté Moins Atteintunclassified